A qualitative study exploring nurses’ attitudes, confidence, and perceived barriers to implementing a traumatic brain injury nursing chart in Uganda - Wynveen, Leslie; Nabulime, Josephine; Luggya, Tonny; Kalanzi, Joseph K.; Mowafi, Hani (African journal of emergency medicine, 2018)
In Africa, traumatic brain injuries frequently result from road traffic injuries and assaults. Despite limited resources and the high costs of life-saving neurosurgical interventions, secondary brain injury prevention has the potential for improving outcomes. However, nurses and other medical personnel infrequently monitor vital signs, blood sugar, and pulse oximetry and only sporadically re-assess neurological status. In one-on-one, semi-structured interviews, 27 nurses from Mulago Hospital’s emergency centre, a tertiary care trauma hospital in Kampala, Uganda, provided feedback regarding a traumatic brain injury-focused education session and use of a nursing chart for detecting secondary brain injury. The interviews explored the nurses’ confidence and perceived barriers to long-term chart implementation and traumatic brain injury care, as well as their ideas for improving this intervention. Interviews were audio recorded, transcribed, and coded using ATLAS.ti: Qualitative Data Analysis and Research Software (Cleverbridge, Inc., Chicago, USA) and Microsoft Word and Excel (Microsoft Office, Redmond, USA) for thematic content analysis. Key findings identified in the interviews included the nurses’ attitudes toward the chart and their feelings of increased confidence in assessing and caring for these patients. The main barriers to continuous implementation included inadequate staffing and resources. Nurses were receptive to the education session and nursing chart, and felt that it increased their confidence and improved their ability to care for traumatic brain injured patients. However, lack of supplies, overwhelming numbers of patients, and inadequate staffing interfered with consistent monitoring of patients. The nurses offered various suggestions for improving traumatic brain injury care that should be further investigated. More research is needed to assess the applicability of a standardised traumatic brain injury nursing education and chart in a broader context.